Intracoronary Adenosine Induced hyperaemia reduces the incidence of myonecrosis due to micro infraction after elective Percutaneous Coronary Intervention - Rajib, MA Rajib; Siddique, Md. Abu; Ahmed, Md. Khurshed; Haque, KMHS Sirajul; Rahman, Md. Mukhlesur; Rahman, Fazlur (University Heart Journal, 2008)
(University Heart Journal 2007; 3 : 73-74)